Impact of Indoor Residual Spraying and Insecticide-treated Bed Nets on Malaria Transmission in Sub-Saharan Africa Using Mathematical Modelling - Tomayer, Andrew (Université d'Ottawa / University of Ottawa, 2016)
Background: Malaria causes over 400,000 estimated deaths annually worldwide, with about 90% in sub-Saharan Africa. Long-lasting insecticidal nets (LLINs) and indoor residual spraying (IRS) are two vector-control interventions proven to reduce malaria transmission, but their use together compared to separate has shown mixed results. Methodology: We used a mathematical model to examine the impact of LLINs and IRS on malaria transmission. Time-series analyses and basic reproductive numbers (R0) were developed using MATLAB. We also assessed IRS timing and performed a sensitivity analysis on R0. Results: Modelling scenarios combining LLINs with IRS were similar to those with LLINs alone. Shorter IRS impulses had greater reductions in mosquito populations. The LLIN feeding-inhibition rate was a key parameter with a negative correlation to R0. Discussion/Conclusion: We developed an understanding of the effect of vector-control strategies on malaria transmission. IRS, when paired with LLINs, showed only small improvements in reducing malaria transmission compared to LLINs alone. These results can assist vector-control programmes.
Keywords: Malaria; Mathematical modelling; Long-lasting insecticidal nets; Indoor residual spraying; Vector control